2014
DOI: 10.1007/s13760-014-0313-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, pathophysiology and management of chronic migraine: a proposal of the Belgian Headache Society

Abstract: Chronic migraine (CM) is a disabling neurological condition affecting 0.5-2 % of the population. In the current third edition of the International Classification of Headache Disorders, medication overuse is no longer an exclusion criterion and CM is diagnosed in patients suffering from at least 15 headache days per month of which at least eight are related to migraine. CM is difficult to treat, and preventive treatment options are limited. We provide a pathogenetic model for CM, integrating the latest findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 127 publications
2
13
0
Order By: Relevance
“…MRI is the imaging modality of choice. However, one study reported normal MR (DWI) brain imaging in a comatose patient with AOP ischemic infarction [ 14 ]. The MRI (DWI) images in Percheron artery infarction can be classified as bilateral paramedian thalamic with rostral midbrain infarction (BPTRMI), bilateral paramedian thalamic without midbrain infarction (BPTWMI), bilateral paramedian and anterior thalamic with midbrain infarction (BPATMI), and bilateral paramedian and anterior thalamic without midbrain infarction [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…MRI is the imaging modality of choice. However, one study reported normal MR (DWI) brain imaging in a comatose patient with AOP ischemic infarction [ 14 ]. The MRI (DWI) images in Percheron artery infarction can be classified as bilateral paramedian thalamic with rostral midbrain infarction (BPTRMI), bilateral paramedian thalamic without midbrain infarction (BPTWMI), bilateral paramedian and anterior thalamic with midbrain infarction (BPATMI), and bilateral paramedian and anterior thalamic without midbrain infarction [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology and pathogenesis of migraine are still poorly understood [ 4 ]. Epidemiological studies found that there is a genetic and familial predisposition for migraine [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Algorithms are already starting to be proposed to treat patients suffering from chronic and refractory migraine [90], but their rationale is based on limited data. With a refractory migraine patient, the intervention consists in tertiary prevention: trying to reduce the deficits and functional disabilities deriving from chronic headache and drug overuse; optimizing symptomatic treatment; trying prophylactic treatments and looking for possible therapeutic alternatives.…”
Section: Concentrations and Effects Of Caffeine May Be Increasedmentioning
confidence: 99%